GAMBARAN PENGETAHUAN DAN PERILAKU REMAJA PUTRI TENTANG PERSONAL HYGINE SAAT MENSTRUASI DI SMK 2 TEMBILAHAN TAHUN 2019 - Almalinda; Yoneta Oktaviani (Jurnal Kesehatan Husada Gemilang, 2020)
In Indonesia, there were 63 million teenagers at risk of unhealthy behavior, since the cleanliness of reproductive organs got less cared for during menstruation. The number of infectious diseases that occur in the reproductive tract of adolescents (10-18 years old), about 35-42%, young adults (18-22 years) 27-33%. This study aims to determine the personal hygiene during menstruation for adolescent girls at SMK 2 Tembilahan in 2019, information for students to maintain personal hygiene, especially during menstruation. The type of the research is quantitative with a descriptive cross-sectional research design about description of the adolescent girls’ knowledge and behavior on personal hygiene during menstruation. There were 73 populations with total sampling. The questionnaire were completed by the respondents, which then analyzed through the used of univariate analysis. This research was conducted on the students of grade X and XI at SMK 2 Tembilahan in 2019. The results shows that adolescent girls with poor knowledge about personal hygiene during menstruation (75.3%) were in the poor category, and well-behaved adolescent girls on personal hygiene during menstruation (54.8%) were in the poor category. These confirm that the students’ knowledge about personal hygiene during menstruation is poor, some of them are good, and the students’ behavior on the personal hygiene during menstruation is good. Accordingly, this result brings a bright light to the adolescent students to take care of their personal hygiene, especially during menstruation.